2019
DOI: 10.1093/imrn/rnz028
|View full text |Cite
|
Sign up to set email alerts
|

Fox H-kernel and θ-deformation of the Cauchy Two-Matrix Model and Bures Ensemble

Abstract: A θ-deformation of the Laguerre weighted Cauchy two-matrix model, and the Bures ensemble, is introduced. Such a deformation is familiar from the Muttalib-Borodin ensemble. The θ-deformed Cauchy-Laguerre two-matrix model is a two-component determinantal point process. It is shown that the correlation kernel, and its hard edge scaled limit, can be written as the Fox H-functions, generalising the Meijer G-function class known from the study of the case θ = 1. In the θ = 1 case, it is shown Laguerre-Bures ensemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…This is very interesting since the former constitutes a Pfaffian point process, while the latter corresponds to a determinantal point process. Also, very recently, Muttalib-Borodin kind of deformation has been considered in the Cauchy two-matrix model and the unrestricted Bures-Hall ensemble by Forrester and Li [55]. Furthermore, Hu and Li have shown that the partition function of the unrestricted trace Bures-Hall ensemble can be identified as the τ -function of BKP and DKP hierarchies [56].…”
Section: Unrestricted Trace Bures-hall Ensemblementioning
confidence: 99%
“…This is very interesting since the former constitutes a Pfaffian point process, while the latter corresponds to a determinantal point process. Also, very recently, Muttalib-Borodin kind of deformation has been considered in the Cauchy two-matrix model and the unrestricted Bures-Hall ensemble by Forrester and Li [55]. Furthermore, Hu and Li have shown that the partition function of the unrestricted trace Bures-Hall ensemble can be identified as the τ -function of BKP and DKP hierarchies [56].…”
Section: Unrestricted Trace Bures-hall Ensemblementioning
confidence: 99%
“…In the case when θ = 1, the corresponding ensembles have been studied in [33][34][35][36][37]. Among other results in [40], the k-point (1 ≤ k ≤ m) correlation function of the unconstrained ensemble is shown to follow a Pfaffian point process…”
Section: Average Entropies Over Interpolating Ensemblementioning
confidence: 97%
“…. , m. This ensemble has been recently studied in [40] in connection to a θ-deformed Cauchy-Laguerre two-matrix model. In the case when θ = 1, the corresponding ensembles have been studied in [33][34][35][36][37].…”
Section: Average Entropies Over Interpolating Ensemblementioning
confidence: 99%
See 2 more Smart Citations